Comparison of Accuracy Scores between CLOC and RSCLO Scoring Systems in Predicting the Risk of Preoperative Laparoscopic Cholecystectomy Conversion at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Nurhayat Usman; Bambang Am Am Sulthana; Reza Syahrial Adiguna (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Cholecystectomy is a surgical therapy for cholelithiasis which can be performed by open cholecystectomy or laparoscopic cholecystectomy. Not all laparoscopic cholecystectomy procedures work properly. Sometimes it requires conversion from laparoscopic cholecystectomy to open cholecystectomy. A risk factor scoring system has been developed and validated using a large prospective cholecystectomy database and can accurately predict the likelihood of conversion with the conversion from laparoscopic to open cholecystectomy (CLOC) score and risk score for conversion from laparoscopic to open cholecystectomy (RSCLO). This study aimed to compare the accuracy value between CLOC and RSCLO in predicting the risk of preoperative laparoscopic cholecystectomy conversion at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Methods: This study was an observational study with a cross-sectional approach. A total of 183 research subjects participated in this study. Observation of CLOC and RSCLO scores was carried out in this study. Univariate and bivariate data analysis was carried out using SPSS. The analysis of the value of sensitivity, specificity, positive predictive value, and negative predictive value were carried out using Medcalc software. Results: A CLOC score > 5.5 has a greater conversion risk than a CLOC score ≤ 5.5. Meanwhile, an RSCLO score >-2 has a greater conversion risk than an RSCLO score ≤ -2. Sensitivity value CLOC for the prediction of preoperative conversion from laparoscopic cholecystectomy to open cholecystectomy obtained 75% and a specificity of 74.85%, with value negative predictive value, which is higher than a positive predictive value and 74.86% accuracy. The sensitivity value RSCLO for the prediction of preoperative conversion from laparoscopic cholecystectomy to open cholecystectomy was obtained at 75% and a specificity of 77.78%. With value negative predictive value, which is higher than the positive predictive value and 74.86% accuracy. Conclusion: The CLOC and RSCLO scores were equally accurate in predicting preoperative conversion from laparoscopic cholecystectomy to open cholecystectomy.